2009
DOI: 10.3748/wjg.15.4429
|View full text |Cite
|
Sign up to set email alerts
|

Sustained virological response in a predominantly hepatitis C virus genotype 4 infected population

Abstract: AIM:To assess sustained virological response (SVR) rates in a predominantly hepatitis C virus (HCV) genotype 4 infected population. Between 2003Between -2007 patients who were treated for chronic hepatitis C infection at our center were included. Epidemiological data, viral genotypes, and treatment outcomes were evaluated in all treated patients. Patients with chronic renal failure, previous non-responders, and those who relapsed after previous treatment were excluded from the study. Among all patients, 57% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…In most of the studies, the SVR rates vary from 44 to 83%, with higher SVR rates in HCV genotype 2 and 3. Studies indicate that, among patients infected with HCV genotype 3, SVR was achieved in 68-83% patients [20][21][22][23][24][25]. However, studies carried out in the Indian population have shown poor response to therapy [6,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the studies, the SVR rates vary from 44 to 83%, with higher SVR rates in HCV genotype 2 and 3. Studies indicate that, among patients infected with HCV genotype 3, SVR was achieved in 68-83% patients [20][21][22][23][24][25]. However, studies carried out in the Indian population have shown poor response to therapy [6,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, with lesser impact, include age, gender, race, bodyweight/body mass index (BMI), and the degree of fibrosis [10,11,[13][14][15][16][17][18][19]. Treatment with PEG-IFN and RBV in CHC yields SVR rates of 44-83%, with higher SVR rates seen in patients infected with HCV genotypes 2 and 3 [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of pegylated IFN compounds in combination with ribavirin, the efficacy of treatment in HCV-4 further improved significantly. In various studies from European and Middle Eastern countries, SVR rates ranging from 43% to 70% were reported [39,40,53,[75][76][77][78][79][80][81][82][83][84][85][86][87][88]73,[89][90][91] (Table 1). These results are indeed higher than those (42-46%) achieved in genotype 1 patients but still lower than those (76-82%) reported in chronic hepatitis C genotype 2 and 3.…”
Section: Evolution Of Treatmentmentioning
confidence: 97%
“…Data for the efficacy of standard combination therapy with Peg-IFNα plus ribavirin in genotype 4 comes mainly from endemic areas such as Egypt [8,9,12,14], Saudi Arabia [10], Kuwait [13] and Quatar [11]. The reported SVRs range between 59.7 and 67.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the efficacy of current combination therapy with pegylated interferon-α (Peg-IFNα) plus weight-based ribavirin is limited and contradictory; sustained virological response (SVR) rates of more than 60% reported in endemic areas [8][9][10][11][12][13][14] are approximately two times higher than those encountered in Europe [15][16][17]. In Greece, genotype 4 accounts for about 15% of all HCV infections [18][19][20][21][22] and is generally considered as "difficult to treat" in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%